2016
DOI: 10.1007/s12011-016-0767-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc Oxide Modulates Antioxidant Capacity, Small Intestine Development, and Jejunal Gene Expression in Weaned Piglets

Abstract: The current study was conducted to investigate the effects of dietary zinc oxide (ZnO) on the antioxidant capacity, small intestine development, and jejunal gene expression in weaned piglets. Ninety-six 21-day-old piglets were randomly assigned to three dietary treatments. Each treatment had eight replicates with four piglets per replicate. The piglets were fed either control diet (control) or control diet supplemented with in-feed antibiotics (300 mg/kg chlortetracycline and 60 mg/kg colistin sulfate) or phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 43 publications
10
43
0
1
Order By: Relevance
“…A previous study has identified a positive correlation between swine weight and the abundance of the family Spirochaetaceae (Unno et al, 2015). Similarly, the increased proportion of Spirochaetaceae by dietary high ZnO supplementation observed in this study may be linked to our early observation that dietary high ZnO improved BW of weaned piglets (Zhu et al, 2017). Furthermore, the percentages of Verrucomicrobia were significant higher in ZnO group or antibiotics group in the ileum.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A previous study has identified a positive correlation between swine weight and the abundance of the family Spirochaetaceae (Unno et al, 2015). Similarly, the increased proportion of Spirochaetaceae by dietary high ZnO supplementation observed in this study may be linked to our early observation that dietary high ZnO improved BW of weaned piglets (Zhu et al, 2017). Furthermore, the percentages of Verrucomicrobia were significant higher in ZnO group or antibiotics group in the ileum.…”
Section: Discussionsupporting
confidence: 70%
“…A total of ninety-six crossbred barrows (Duroc × Landrace × Large White) weaned at 21-day-old, with an initial body weight (BW) of 5.99 ± 0.04 kg, were used in this study, as described in our recent study (Zhu et al, 2017). Briefly, piglets were randomly allotted to three dietary treatment groups: (1) control group (piglets were fed basal diet without any in-feed antibiotics); (2) antibiotic group (piglets were fed the basal diet with in-feed antibiotics of 300 mg/kg chlortetracycline and 60 mg/kg colistin sulfate); and (3) ZnO group (piglets were fed the basal diet with 3,000 mg/kg ZnO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29-31 For instance, a decrease of diarrhoea incidence was accompanied by an increase in villus height of the duodenum and ileum and a decrease in crypt depth of the duodenum in weaned piglets with ZnO-supplemented diets. 30 Changes in VH and CD are considered key measurements for the assessment of gut maturation and nutritional effects. 32 There are many published papers on the crosstalk of diarrhoea and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Piglets at 65 days of age were weighed again and the average daily weight gain of piglets within each breed was calculated. At the end of the experiment, all piglets were slaughtered for sample collections as previously described (Zhu et al, 2017 ). Fresh ileum and colon mucosa, and colon contents were collected and shock-frozen in liquid nitrogen, then stored at −80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%